2012
DOI: 10.5402/2012/820653
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Enhancement of Etoricoxib by Cosolvency Approach

Abstract: The purpose of the present study was to examine and compare the cosolvency using three different cosolvents, namely PEG 400, PG, and glycerin on the aqueous solubility enhancement of a poorly aqueous soluble drug, etoricoxib, since solubilization of nonpolar drugs constitutes one of the important tasks in the formulation design of liquid dosage forms. The aqueous solubility of etoricoxib was 0.0767 ± 0.0018 mg/mL, which was significantly improved by the addition of PEG 400, PG, and glycerin as cosolvents. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 14 publications
(17 reference statements)
1
51
0
1
Order By: Relevance
“…There has been only one publication reporting the solubility of etoricoxib in organic solvents. Nayak and Panigrahi 85 examined the solubility enhancement of etoricoxib using the cosolvency method. The very low aqueous solubility of etoricoxib can cause problems in preparing drug formulations, and can limit the drug's effectiveness by delaying the rate of absorption and onset of therapeutic action.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…There has been only one publication reporting the solubility of etoricoxib in organic solvents. Nayak and Panigrahi 85 examined the solubility enhancement of etoricoxib using the cosolvency method. The very low aqueous solubility of etoricoxib can cause problems in preparing drug formulations, and can limit the drug's effectiveness by delaying the rate of absorption and onset of therapeutic action.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…DSC and XRD simultaneously suggested the loss of drug crystallinity of upon liquisolid formulation which was further confirmed and validated by SEM that ensured the superiority of the technique. Bioavailability study indicated that the prepared optimal liquisolid formula did not differ significantly from the marketed famotidine tablets concerning C max , t max , and AUC (0)(1)(2)(3)(4)(5)(6)(7)(8) Figure 2). The role of nonvolatile solvents in enhancement of dissolution behavior can be easily observed by analyzing the obtained dissolution data, but the burden of further increment in these pharmaceutical parameters, falls on nature and type of carrier material used.…”
Section: Investigations Reported In 2008mentioning
confidence: 96%
“…As mentioned before solubility enhancement ratio was compared with midazolam water solubility. This different range can be explained by P.G and PEG400 dielectric constant which is 32 and 12.4, respectively 16 . The dielectric constant of phosphate buffer solution with the same ionic strength has been assumed78.5 in previous reports 34 .…”
Section: Hpmc Effectmentioning
confidence: 99%
“…They can reduce the interfacial tension between the aqueous solutions and disrupt waters selfassociation and reduce hydrophobic solute squeeze out. The most frequently used low toxic and due to their cilio-friendlyco-solvents for nasal use are propylene glycol, glycerin, polyethylene glycol (PEG), etc 16,32,33 .…”
Section: Hpmc Effectmentioning
confidence: 99%
See 1 more Smart Citation